ATM mutation rather than BIRC3 deletion and/or mutation predicts reduced survival in 11q-deleted chronic lymphocytic leukemia: data from the UK LRF CLL4 trial - Rose-Zerilli, M. J. J.; Forster, J.; Parker, H.; Parker, A.; Rodriguez, A. E.; Chaplin, T.; Gardiner, A.; Steele, A. J.; Collins, A.; Young, B. D.; Skowronska, A.; Catovsky, D.; et al. (Haematologica (Roma), 2014)
ATM mutation and BIRC3 deletion and/or mutation have independently been shown to have prognostic significance in chronic lymphocytic leukemia. However, the relative clinical importance of these abnormalities in patients with a deletion of 11q encompassing the ATM gene has not been established. We screened a cohort of 166 patients enriched for 11q-deletions for ATM mutations and BIRC3 deletion and mutation and determined the overall and progression-free survival among the 133 of these cases treated within the UK LRF CLL4 trial. SNP6.0 profiling demonstrated that BIRC3 deletion occurred in 83% of 11q-deleted cases and always co-existed with ATM deletion. For the first time we have demonstrated that 40% of BIRC3-deleted cases have concomitant deletion and mutation of ATM. While BIRC3 mutations were rare, they exclusively occurred with BIRC3 deletion and a wild-type residual ATM allele. In 11q-deleted cases, we confirmed that ATM mutation was associated with a reduced overall and progression-free survival comparable to that seen with TP53 abnormalities, whereas BIRC3 deletion and/or mutation had no impact on overall and progression-free survival. In conclusion, in 11q-deleted patients treated with first-line chemotherapy, ATM mutation rather than BIRC3 deletion and/or mutation identifies a subgroup with a poorer outcome.